Bending collapse analysis for thin and medium-thin-walled square and rectangular hollow shapes - Lavayen-Farfan, D.; Boada, M.J.L.; Rodriguez-Hernandez, J.A. (Elsevier, 2021)
Thin-walled hollow shapes are of great interest in many industries with weight constraints due to their availability, low price, and strength to weight ratio. However, they are also prone to localized bending collapse, which can be used as an energy absorption mechanism during deformation. Up until now, industrial applications have relied on numerical simulations, non-standardized tests, and a handful of theories to address the bending collapse behavior. In this paper, a modification to the most widely used theory is presented and adapted for hollow shapes with greater thickness that cannot be considered “thick”. To verify the accuracy of the proposed modification, a comparison with a detailed FEM model, validated through various three-point bending collapse experimental tests, has been performed. The results seem to show that the proposed modifications can predict the maximum load and collapse stage behavior of hollow shapes with more accuracy than the original analytical model. Thus, the proposed modification may be used to predict the collapse behavior of commercially available square and rectangular hollow shapes in different fields of application.
Keywords: Bending; Square (algebra); Structural engineering; Finite element method; Deformation (meteorology); Materials science; Mechanics; Composite material; Geometry; Engineering; Mathematics; Physics; https://purl.org/pe-repo/ocde/ford#2.01.02